Characterization of IL‐22 and IL‐17 Expressing Leukocytes in the Cervix. (13th October 2015) - Makinde, Hadijat M.; Lurain, Nell; Bitterman, Pincas; Martinson, Jeff; Plants, Jill; Landay, Alan L.; Spear, Greg T.
Abstract : Problem: Identification of the types of cells that produce IL‐17 and IL‐22 in the genital tract can clarify the roles that these cytokines play in responses to pathogens. Method of study: We isolated and stimulated cells from cervical tissue to identify and characterize cytokine‐producing cells. Results: Upon stimulation of CD3 + CD4 + endocervical cells, 1.6, 3.4, and 1.5% were induced to produce IL‐22, IL‐17, and both cytokines, respectively. Stimulation of CD3 + CD4 + ectocervical cells resulted in 3.3% IL‐22 +, 5.5% IL‐17 + and 2.6% IL‐22 + IL17 + cells. CD45 + CD3 − cells had relatively high endogenous levels of cytokine expression that did not increase upon stimulation. Innate lymphoid cells (ILCs) made up 5.7–8% of CD45 + cervical cells and stimulation caused increases in IL‐17 and IL‐22. Conclusion: These studies show that the majority of the CD45 + leukocytes that can be induced to produce IL‐22 and IL‐17 in cervix are CD3 + CD4 +, but ILCs are also present and can make both cytokines.